Love and Spirituality in Leylâ ile Mecnûn: A Cultural Study of Ottoman Sufi Poetry - Fathimah Az Zahro (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2025)
This paper examines Fuzûlî’s Leylâ ile Mecnûn as a complex work of Ottoman Islamic literature. It goes beyond being a love story and acts as a spiritual, cultural, and psychological text. Using recent studies on Sufi poetry, Ottoman culture, and manuscript illustrations, this paper explores how Fuzûlî changes the classic Majnûn-Layla story into a mystical allegory. This allegory represents a divine longing (maḥabba), a letting go of the self (fanā’), and spiritual knowledge (ma‘rifa). The poem uses symbols, metaphors, and themes showing the Islamic mystical tradition and the Ottoman sociocultural environment. Using local folk elements, court rituals, and powerful images, the poem becomes a way to teach spiritual lessons to the elite and the citizens. In addition, the study studies the visual aspects of illustrated manuscripts and how the poem sounds when performed, which further emphasizes its spiritual message. The poem's connections to earlier Arabic and Persian sources are reinterpreted through an Ottoman perspective. This paper concludes that Leylâ ile Mecnûn is more than a romantic epic. It is a cultural and devotional object showing the spiritual imagination of the Ottoman Islamic world and connecting literature, mysticism, and identity through a shared poetic story.